Malaria Strategic Plan - Malawi Government: Ministry of Health (Malawi Government, 2021)
Malaria is a major public health problem in Malawi. It is the leading cause of morbidity and mortality in children under five years of age and pregnant women. It is the most common cause of outpatient visits, hospitalization and death. Malaria is also a development problem as it has a serious socio-economic impact on families and the nation, through loss of work, school absenteeism and high levels of expenditure on treatment. The government of Malawi through the Ministry of Health and its partners are committed to controlling malaria in the country. As part of the malaria control strategies, the Ministry has developed several guiding malaria documents one of which is the National Malaria Strategic Plan for 2005 to 2010. Using the Strategic Plan as a guide, Annual Action Plans will be developed every year. While the purpose of the Malaria Strategic Plan for 2001 to 2005 encompassed renewed efforts to reduce malaria morbidity and mortality in the context of multi-sectoral implementation of malaria control activities, the Malaria Strategic plan for 2005 to 2010 will focus on “scaling up” of malaria control activities in the context of the Essential Healthcare Package (EHP) and sector-wide approaches. The main strategic areas that have been identified for the scale-up of malaria control activities, include, among others, Malaria Case Management, Intermittent Preventive Treatment (IPT) of pregnant women with SP and malaria prevention with special emphasis on the use of Insecticide Treated Mosquito Nets (ITNs). I am hopeful that concerted efforts to implement this Malaria Strategic Plan with the support of global, regional and national partners will enable Malawi to significantly reduce the health and socioeconomic burden of malaria.